2021
DOI: 10.1016/j.bbi.2021.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric and neuropsychiatric sequelae of COVID-19 – A systematic review

Abstract: It has become evident that coronavirus disease 2019 (COVID-19) has a multi-organ pathology that includes the brain and nervous system. Several studies have also reported acute psychiatric symptoms in COVID-19 patients. An increasing number of studies are suggesting that psychiatric deficits may persist after recovery from the primary infection. In the current systematic review, we provide an overview of the available evidence and supply information on potential risk factors and underlying biological mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
320
4
16

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 341 publications
(353 citation statements)
references
References 112 publications
(354 reference statements)
13
320
4
16
Order By: Relevance
“…6 Studies conducted on patients infected with COVID-19 more than one third showed neurologic symptoms in the acute phase of the disease and about 34% showed brain abnormalities such as white matter hyperintensity and hypodensity as well as microbleeding, hemorrhage and infarction. 7 Further evidence of SARS-CoV-2 neuroinfection, edema and neuronal degeneration were reported in post-mortem brain samples, while in the case of encephalitis genome sequencing confirmed the presence of the virus in the cerebrospinal fluid. However, histopathological findings from autopsies of 18 consecutive patients with SARS infection -CoV-2 who died in a teaching hospital between April 14 and April 29, 2020 showed hypoxic changes and did not exhibit encephalitis or other virus-specific brain changes.…”
Section: Neuropathology In Covid-19 Infectionmentioning
confidence: 93%
See 4 more Smart Citations
“…6 Studies conducted on patients infected with COVID-19 more than one third showed neurologic symptoms in the acute phase of the disease and about 34% showed brain abnormalities such as white matter hyperintensity and hypodensity as well as microbleeding, hemorrhage and infarction. 7 Further evidence of SARS-CoV-2 neuroinfection, edema and neuronal degeneration were reported in post-mortem brain samples, while in the case of encephalitis genome sequencing confirmed the presence of the virus in the cerebrospinal fluid. However, histopathological findings from autopsies of 18 consecutive patients with SARS infection -CoV-2 who died in a teaching hospital between April 14 and April 29, 2020 showed hypoxic changes and did not exhibit encephalitis or other virus-specific brain changes.…”
Section: Neuropathology In Covid-19 Infectionmentioning
confidence: 93%
“…The occurrence of an exaggerated immune response known as a cytokine storm. 7 When a cytokine storm occurs, there will be excessive production of cytokines causing acute respiratory distress syndrome (ARDS) and multiple organ dysfunction syndrome (MODS) which lead to a number of diseases. other complications, especially from the CNS.…”
Section: Neuropathology In Covid-19 Infectionmentioning
confidence: 99%
See 3 more Smart Citations